EDUCATIONAL NEEDS OF OLDER ADULTS - Pivoriene, Jolanta; Zemaitaityte, Irena; Bardauskiene, Raminta; Katkoniene, Agata; Sadauskas, Justinas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The aim of the article is to find out educational needs of older adults and to discuss the process of the training course development and its implementation jointly with older learners in Lithuania. Mixed methods research was applied incorporating survey and participatory research. The training course was developed based on international survey data aiming to reach older learners who had less possibilities to engage in a lifelong learning process. Data analysis revealed similarities across countries, based on which the general template of the course was developed. It included topics in biological, psychological and sociological aspects of ageing, networking and joint research possibilities. However, data showed that there were variations in needs not only between countries but inside countries as well. Participatory research approach allowed older learners to follow the needs and to make necessary changes. Such changes were made in content (for ex., some sociological topics substituted by culture) and in organization (less intensity and shorter sessions) of the course. Even if the learners agreed to involve in participatory research, at the end they were told that it was too many interviews and discussions. On the other hand, they were proud that other learners will take their designed course.